Analisis Keuangan Usaha Mikro Kecil Di Kota Palangka Raya - Benius Benius; Aisyah Mecca; Khairun Nisa; Meta Melinda Aldis; Nita Beti Lestari; Yula Yunara (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This research aims to analyze financial management in four types of small MSME businesses in Palangka Raya City, namely the coconut ice business, the Gambang bread business, the meatball business, and the crepes business. The analytical methods used include liquidity analysis, profitability ratios, and common size analysis to understand the financial performance of each business. Data was collected through interviews with business owners and collecting financial data from business records. The results of the analysis show variations in financial management between the four types of businesses, with findings highlighting the specific challenges and opportunities facing each type of business. The implications of this research provide valuable insights for business owners and other stakeholders in improving financial management and financial performance of small MSMEs in Palangka Raya City.